Initial experience and validation of a novel tool to assess patient experience in the catheterization laboratory (PATCATH), in patients undergoing coronary angiography or angioplasty. (2nd July 2022) - Wilson, H; Brenan, M; Rai, H; Blake, N; Mccann, H; Blake, G; Colleran, R; Hanratty, C; Begossi, N; Byrne, R A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patient-reported experience metric (PREM) questionnaires are an important tool for evaluating patient experience. Purpose: Validated PREM tools may help to identify areas of quality improvement within healthcare. Methods: A novel tool developed by the Patient Initiative Committee of the European Association of Percutaneous Intervention (EAPCI), in association with the European Society of Cardiology Patient Forum was designed to capture patient experience in the catherization laboratory. The questionnaire is divided into 3 domains assessing experience before, during and after coronary angiography or angioplasty (Figure 1, Panels A-C). Responses were recorded on a scale of strongly agree, agree, disagree, or strongly disagree. Consecutive patients undergoing a coronary angiography or angioplasty received the questionnaire to complete anonymously during recovery following catheterization. Results: A total of 100 valid responses were received over a four week pilot experience. Most patients had an angiogram procedure (80%). A total of 52% were grouped in the higher age category (≥66 years) (Table 1). Patient response indicated a high level of satisfaction with the experience before the procedure: 98.6% of patients strongly agreed or agreed with statements assessing positive experience reflecting a level of knowledge of why the procedure was recommended and perceived level of support (Figure 1, Panel A). 98.5% strongly agreed or agreed with statements assessing positive experience of comfort, safety, communication and understanding during the procedure (Figure 1, Panel B). A total of 9.6% of patients within the higher age category provided no response regarding their understanding for why a treatment decision was made, whilst all patients in the lower age category responded. After the procedure, 59.3% strongly agreed or agreed with statements assessing positive experience: with lower levels of positive experience for questions related to lifestyle changes (60%), comprehension of a rehabilitation program (46%), medication prescription (58%) and treatment duration (53%) (Figure 1, Panel C). However, 15.2% of questions in this domain had no response, particularly those related to prescribed medication. A lower positive experience was observed between higher versus lower age categories respectively (44.2% & 77.1%) regarding an understanding of necessary lifestyle changes. Conclusion: The results of our initial experience with a novel PREMs tool highlight high levels of positive experience before and after diagnostic angiography and a lower level of positive experience in the period after the procedure. Completing this tool at a later stage or post-hospital discharge (i.e., following additional education interventions) may help to capture a higher positive response related to after the intervention. To validate these findings, this PREM tool should be evaluated further in additional patient cohorts across multiple sites.